2021
DOI: 10.1167/iovs.62.6.21
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Retinal Ganglion Cell Loss By a Novel ROCK Inhibitor (E212) in Ischemic Optic Nerve Injury Via Antioxidative and Anti-Inflammatory Actions

Abstract: This study investigated the neuroprotective effects of administration of ROCK inhibitor E212 on ischemic optic neuropathy. METHODS.Rats received an intravitreal injection of either E212 or PBS immediately after optic nerve infarct. The oxidative stress in the retina was detected by performing superoxide dismutase activity and CellROX assays. The integrity of retinal pigment epithelium was determined by staining of zona occludens 1. The visual function, retinal ganglion cell (RGC) density, and RGC apoptosis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 76 publications
(86 reference statements)
0
12
0
1
Order By: Relevance
“…The procedure has been described in detail in our previously published reports [ 7 , 21 , 22 , 23 , 30 , 31 ]. Briefly speaking, after ONC, fVEPs were recorded 14 days later by a visual electrodiagnostic system (Espion, Diagnosys LLC, Gaithersburg, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure has been described in detail in our previously published reports [ 7 , 21 , 22 , 23 , 30 , 31 ]. Briefly speaking, after ONC, fVEPs were recorded 14 days later by a visual electrodiagnostic system (Espion, Diagnosys LLC, Gaithersburg, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed steps have been described in our previous reports [ 7 , 21 , 22 , 23 , 30 , 31 ]. Briefly, the retrograde labeling of the RGCs was performed 7 days before the rats were euthanized on day 14.…”
Section: Methodsmentioning
confidence: 99%
“…Although the experimental studies are limited to investigating the pathophysiology of oxidative stress in NAION, some studies using antioxidants to treat NAION showed prolonged RGC survival [ 175 , 237 , 238 ]. In addition to glaucoma, brimonidine and Rho kinase inhibitors demonstrated antioxidative function and neuroprotective properties in ischemic optic neuropathy [ 237 , 238 ], and fasudil, one specific Rho kinase inhibitor, has been investigated in human subjects [ 239 ].…”
Section: Potential Antioxidant Therapy For Retinal Ganglion Cell Degenerationsmentioning
confidence: 99%
“…At the same time, disc swelling and compartment syndrome further induce oxidative stress [4,[9][10][11][12]. Oxidative stress promotes the development of neuroinflammation and the loss of RGCs [12][13][14][15]. However, the complete mechanism constituting the cause of this chain reaction is still unknown.…”
Section: Introductionmentioning
confidence: 99%